Status Construction During COVID-19: Antibody Positive People's Rising Prestige - Evans, M. D. R.; Kelley, Jonathan; Kelley, Sarah (Frontiers in Sociology, 2020)
The protracted COVID-19 crisis provides a new social niche in which new inequalities can emerge. We provide predictions about one such new inequality using the logic of Status Construction Theory (SCT). SCT is rooted in Expectations State Theory and from there developed by Ridgeway and colleagues, proposes general hypotheses about how new inequalities arise through process of interaction at the individual level: an unordered categorical differences becomes attached to a cultural value that gives one category more value than the other; social scripts concerning it emerge; small elements of assertion and deference creep into more and more encounters that an individual participates in, hears about through networks, and learns about via social and conventional media. The categorical difference begins to morph into a hierarchical status distinction. Through these mechanisms, individuals develop "status beliefs" that most people in their communities endorse the status distinction. Although they may or may not endorse the distinction personally, they believe that most people do so and they find that the path of least resistance socially is to enact the scripts that affirm the higher status/prestige of the favored group. We apply Status Construction Theory to the categorical difference between Antibody Positives (who have been tested for IgG antibodies) and Others (everybody else). Using the general logic of SCT and specifically developing applications of its key propositions, we predict that the categorical difference between Antibody Positives and Others will transition to a status distinction and propose testable, falsifiable hypotheses about each step of the process.